EFFICACY OF PROTAPER NEXT AND PROTAPER UNIVERSAL RETREATMENT SYSTEMS IN REMOVING GUTTA-PERCHA IN CURVED ROOT CANALS DURING ROOT CANAL RETREATMENT - Taha ÖZYÜREK; Ebru ÖZSEZER-DEMİRYÜREK (Istanbul University, 2017)
Purpose: The aim of this study was to compare the cleanliness of root canal walls after retreatment using ProTaper Next (PTN), ProTaper Universal Retreatment (PTR) nickel-titanium (NiTi) systems and Hedström hand files in curved mesial canals of mandibular molar teeth and the time required for gutta-percha and sealer removal. Materials and Methods: Ninety mandibular molar teeth with curved mesial roots were instrumented up to #35.04 with Mtwo NiTi rotary instruments and obturated using the continuous wave of condensation technique. Removal of gutta-percha and sealer was performed using one of the following: PTN and PTR NiTi systems and Hedström hand files. Samples were placed on the VistaScan phosphor plates in the mesio-distal direction and the radiographs were taken. The digital radiographs were analyzed using AutoCAD software. Also, the total time required for gutta-percha removal was calculated by a chronometer. Results: The total retreatment time was significantly shorter in the PTN and PTR groups compared with the manual group (p<0.05). There was a significant difference between the groups according to the total residual gutta-percha and sealer (p<0.05). The PTN and PTR groups left significantly less gutta-percha and sealer remnant than the manual group (p<0.001). Conclusion: Within the limitations of this study, the PTN and PTR groups showed less residual gutta-percha and sealer than the manual group. The NiTi rotary systems were significantly faster than the manual group in the time required for gutta-percha and sealer removal.